2012
DOI: 10.1007/s00397-012-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on creeping channel flows of compressible fluids subject to wall slip

Abstract: Creeping channel flows of compressible fluids subject to wall slip are widely encountered in industries. This paper analyzes such flows driven by pressure in planar as well as circular channels. The analysis elucidates unsteady flows of Newtonian fluids subject to the Navier slip condition, followed by steady flows of viscoplastic fluids, in particular, Herschel-Bulkley fluids and their simplifications including power law and Newtonian fluids, that slip at wall with a constant coefficient or a coefficient inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Under the lubrication approximation, Tang (2012) also derived analytical time-dependent solutions of the same flows. As in Tang andKalyon (2008a, 2008b), he assumed that a à $ 1=p à and pointed out that such a dependence, also proposed for low-density compressible flow [Bird et al (2002)], is similar to that of Eq. (2).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Under the lubrication approximation, Tang (2012) also derived analytical time-dependent solutions of the same flows. As in Tang andKalyon (2008a, 2008b), he assumed that a à $ 1=p à and pointed out that such a dependence, also proposed for low-density compressible flow [Bird et al (2002)], is similar to that of Eq. (2).…”
Section: Introductionmentioning
confidence: 85%
“…He showed that, in general, the pressure gradient is not constant and depends on both the inlet and the outlet pressures. Tang andKalyon (2008a, 2008b) also developed a mathematical model describing the time-dependent pressure-driven flow of compressible polymeric liquids subject to pressure-dependent slip. They assumed that the slip coefficient a* is inversely proportional to the pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic experimental study at the capillary rheometer of pressure dependent slip of polyolefins, together with a very thorough mathematical model, is due to Hatzikiriakos and Dealy (1992), while a theoretical study of pressure dependent wall slip of Newtonian fluids without neglecting inertia is due to Rao and Rajagopal (1999). Tang and Kalyon (2008) and Tang (2012) have solved some pressure dependent slip flows of non-Newtonian compressible suspensions and compared them with experimental results obtained using polydimethylsiloxane as a test fluid. More recently, Kalogirou et al (2011), Damianou et al (2013) and Housiadas (2013) have solved theoretically and numerically some flows of incompressible Newtonian and non-Newtonian fluids with pressure dependent slip.…”
Section: Introductionmentioning
confidence: 99%
“…Although pressure driven flows are unidirectional and have been studied earlier for Newtonian and some non-Newtonian fluids, they still attract special attention in a number of emerging problems [16][17][18][19]. Ellahi [11] has examined the effect of the slip condition on flow of an Oldroyd 8-constant fluid in a channel.…”
Section: Introductionmentioning
confidence: 99%